Computing Tower-Footing Grounding Impedance and GPR curves of Grounding Electrodes Buried in Multilayer Soils - Araujo, Anderson R. J. de [UNESP]; Colqui, Jaimis S. L. [UNESP]; Kurokawa, Sergio [UNESP]; Seixas, Claudiner M.; Kordi, Behzad; IEEE (Ieee, 2019)
Grounding systems are essential to dissipate fault currents into soil to guarantee safe conditions to personnel and equipment. In this context, several approaches have been employed to calculate tower-footing grounding impedance either in the frequency or time domain. In the Transmission Line Model (TLM), vertical or horizontal electrodes are represented by distributed parameters along its length. and its impedance are calculate by analytical equations. However, for counterpoise electrodes there are no analytical formulae to estimate its tower-footing grounding impedance. To tackle this issue, numerical methods have been employed to assess the tower-footing grounding impedance in any various arrangements. In this article, a comparison between the grounding impedance obtained by the TLM and numerical Method of Moments (MoM) is carried out in order to verify the accuracy of the numerical method. Then, grounding impedances of counterpoise electrodes and the Grounding Potential Rising (GPR) are calculated for different configurations of a multi-layer soil. It can be noted that grounding impedance of counterpoise electrodes as well as the peaks of the GPR curves are strongly modified by the presence of multi-layer soil and electrode length.
Keywords: electromagnetic transients; transmission tower; tower-footing grounding impedance; multi-layer soils